Production of Biofuel Crops in Florida: Switchgrass - Yoana C. Newman; Curtis Rainbolt; Mary J. Williams; Joao Vendramini (EDIS)
This series of illustrated fact sheets introduces growers to several potential biofuel crops for Florida, with assessments of potential, description of biology, production, potential yields, production challenges and estimated costs, environmental concerns, and references. Published by the UF Department of Agronomy, January 2008.